DESIGN AND DEVELOPMENT OF OXYGEN MONITORING WITH GALVANIC OXYGEN SENSOR BASED ON MICROCONTROLLER ARDUINO UNO - Budi Prijo Sembodo; Nanang Henri Vidal (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2019)
The Oxygen Analyzer is a tool for measuring the oxygen content in a gas exhaust system. The Oxygen analyzer is used in various fields including the fields of industry and health. In the health sector, the Oxygen Analyzer is used to measure oxygen content in Continuous Positive Airway Pressure (CPAP), anesthetic machines, ventilator machines, or oxygen cylinders. In this study the researchers made an Oxygen Analyzer that can read oxygen levels 21% 100% with a reading range per digit. This study uses an oxygen sensor that serves to detect oxygen levels which is set with an Arduino Uno microcontroller. The testing is carried out directly on a ventilator as a comparison tool. The method of data analysis in this study uses descriptive analysis. In this study the tool created was able to detect the value of oxygen levels in the range of 21% - 100% with an average error of 0.01%.